Penerapan Safety Farming di Desa Batu Kali: Upaya Peningkatan Keselamatan dan Kesehatan Kerja Petani - Ismi Elya Wirdati; Heni Rusmitasari; Syakir Maghfuri; Shafira Aulia Az Zahra; Laila Zulvatun Nikmah; Aditya Wisnu Saputra (Lembaga Pengembangan Kinerja Dosen, 2025)
Farmers often face various occupational safety and health (OSH) risks such as exposure to pesticides, physical injuries, ergonomic discomfort, and unsafe working conditions. In Batukali Village, the implementation of agricultural OSH principles is still low, which has an impact on the welfare of farmers. This community service aims to implement a Safety Farming Village, which includes hazard identification, risk management, and risk control through the provision of personal protective equipment (PPE) to improve OSH practices among farmers. The methods used in this community service program included training on OSH implementation through focus group discussions (FGDs), discussions, lectures, and measuring improvements through pre-tests and post-tests, as well as qualitative evaluation through in-depth interviews. The results showed a significant increase in knowledge during the training. Hazard identification and risk management documents were compiled, and there was a reduction in unsafe actions and unsafe conditions, as well as an increase in the effectiveness of the tools used in accordance with ergonomics. The conclusion confirms that the Safety Farming model has the potential to be an effective intervention in agricultural areas and can be replicated